The Effects of Emotional Schema Therapy on Social Health and Attitude Towards Social Harms Among Female Students - Fatemeh Eskandari; Milad Abedi ghlich ghashlaghi (Caspian Journal of Health Research)
Background: In recent studies on adolescents, increasing attention is being given to the social dimension of health, alongside its physical and mental aspects. Objectives: The present study was conducted to determine the effectiveness of emotional schema therapy on social health and attitude towards social harms of female students. Method: The current research is a semi-experimental study with a pre-test, and post-test design involving a control group and a two-month follow-up. The focus of this research was on female students who were enrolled at Honarestans in Shahin Shahr during 2022. Thirty students through a convenience sampling method were selected. Subsequently, using a random dice roll participants were allocated at random to either the experimental (n=15) or the control group (n=15). The emotional schema therapy group participated in 8 one-hour and a half session (one session per week). The research tools used were the attitude towards social harms questionnaire and the social well-being questionnaire. The data was analyzed using a repeated measures analysis of covariance with SPSS software version 28. Results: Repeated measures analysis showed significant group-by-time interactions for attitudes toward social harm (F=22.98, P<0.001, η²=0.46) and social health (F=29.97, P<0.001, η²=0.53). The experimental group demonstrated significant reductions in social harm and improvements in social health from pretest to posttest and follow-up (P<0.05), while no significant changes were observed in the control group. Between-group differences were substantial for both outcomes, with greater changes observed from baseline to follow-up. Conclusion: This study discovered that emotional schema therapy had a beneficial effect on the social welfare of teenage girls enrolled in schools in Shahin Shahr City. It is recommended that schema therapy workshops be organized in educational settings to enhance social well-being.